Dapagliflozin twice daily or once daily: effect on pharmacokinetics and urinary glucose excretion in healthy subjects. Issue 4 (12th January 2015) - Tang, W.; Reele, S.; Hamer‐Maansson, J. E.; Parikh, S.; de Bruin, T. W. A.
<x xml:space="preserve">Abstract</x> The primary objective of this single‐centre, open‐label crossover study (NCT01072578) was to assess the effect of dapagliflozin on the amount of glucose in the blood and urine in healthy volunteers when dapagliflozin was administered once a day (10 mg) versus twice a day (5 mg every 12 h) after 5 days of dosing. At steady state, the AUCss (0‐24) (area under the dapagliflozin curve (0‐24 hours) at steady state), Css, av (average concentration at steady state) between dapagliflozin 5 mg twice daily and 10 mg once daily were similar AUCss(0‐24) [5 mg bid, (458.0 (28.7)) and 10 mg qd, (470.0 (28.5))] and Css, av [5 mg bid 18.8 (28.9)) and 10 mg qd, (19.6(28.5))], but minimum and maximum plasma levels of dapagliflozin differed significantly. Percent inhibition of renal glucose reabsorption (%IRGRA) and total urinary glucose excretion over 24 h were similar for both doses. The relationship between the mean dapagliflozin concentration and %IRGRA and the total urinary glucose excreted was well described by a maximum effect model. The results indicate that dapagliflozin may be used for either once daily or twice daily administration.